(untitled) (Annals of Medical Research, 2022)
Aim: Our aim was to compare the efficacy and complications of self-expanding metal stents (SEMS) in anastomotic leaks related to esophagogastrostomy (EG) and esophagojejunostomy (EJ). Methods: Demographic characteristics, types of surgery, anastomotic leak detection time, clinical findings, diagnostic methods, radiological and endoscopic findings, biochemical findings, efficacy and complications of SEMS, morbidity, and mortality rates of 17 patients who underwent SEMS due to EG (8 cases) or EJ (9 cases) anastomotic leakage after esophageal and gastric tumor resection between 2013-2019 were compared. Mann-Whitney U test was used in the analysis of quantitative variables, Fisher Exact and Fisher-Freeman-Holton tests were used in the analysis of categorical variables. Results: While early term SEMS migration was not observed in the EG group, it was observed in 5 (55.5%) cases in the EJ group (p=0.564). In the EJ group, laceration in the jejunal loop due to SEMS migration was observed in 1 (11.1%) case, and intestinal perforation was observed in 1 (11.1%) case. The amount of anastomotic leakage after SEMS was significantly decreased in the EG group compared to the EJ group (p=0.028). C-reactive protein values were lower and albumin levels were higher in the EG group compared to EJ group (p=0.093, p=0.078, respectively). Mortality was seen in 1 (12.5%) patient in the EG group and in 5 (55.5%) patients in the EJ group (p=0.131). The mean age of those who developed mortality was higher than those who did not (p=0.015). Conclusion: While SEMS is effective in EG anastomotic leakage, its success rate is low in EJ anastomotic leakage.